Analisis Maturitas Tata Kelola Aset Teknologi Informasi di Perusahaan Xyz Menggunakan Cobit 5 Proses BAI09 Manage Assets - Muhammad Hanivan Titunanda; Andi Reza Perdanakusuma; Admaja Dwi Herlambang (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
Evaluation of maturity level is needed in the management of information technology assets owned by Perusahaan XYZ to make the management of information technology assets better. Thus, the performance of Perusahaan XYZ as a bank corporation can be improved. This research uses the COBIT 5 framework. The purpose of this research is to identify the extent to which Perusahaan XYZ has managed its assets and optimizes the cost of IT assets. Data retrieval in this study is by questionnaire, observation and interviews used to support observational data. COBIT 5 is used as a reference for evaluating the process of managing information technology assets. The results of Perusahaan XYZ maturity level assessment through the BAI09 (Manage Assets) process domain found that the maturity level is at level 1 with a L or Largely achieved rating with a percentage of 72.1% where the implemented process has succeeded in achieving its process objectives. Which means the maturity level of information technology asset management in Perusahaan XYZ is at level 1 (Performed process). There is a gap between targeted level and the current level which consist of 1 point. Recommendations for improvement are given so that the process can reach the targeted maturity level which is level 2 (Managed Process).